Military Assistance to Civilians within the Framework of Collaborative Governance in Environmental Management - Yanto S Manurung; Jorry S Koloay; Zuhdizul Zuhdizul (Pusat Studi Pembangunan dan Pemberdayaan, 2026)
Environmental pollution and ecosystem degradation present complex governance challenges that often exceed the capacity of civilian institutions alone, particularly in contexts characterized by weak enforcement and fragmented coordination. In response, governments increasingly involve the military in civilian environmental programs, raising important questions regarding collaborative governance, institutional roles, and legitimacy. This study examines collaborative governance in the context of military assistance to civilians in environmental pollution and damage control, focusing on governance processes rather than environmental outcomes alone. Employing a qualitative research design, data were collected through in-depth interviews with military personnel, civilian government officials, community representatives, and civil society actors, complemented by document analysis. The findings reveal that military involvement enhances coordination, accelerates implementation, and strengthens enforcement legitimacy through its operational capacity and symbolic authority. However, collaboration is characterized by asymmetrical power relations that require careful management to preserve civilian leadership and participatory governance principles. Community acceptance emerges as a critical factor, shaped by inclusive engagement, transparent communication, and adaptive coordination practices. This study contributes to the collaborative governance literature by empirically demonstrating how non-traditional actors can be integrated into civilian-led governance frameworks under real-world constraints. The findings offer policy-relevant insights for designing collaborative environmental governance arrangements that balance effectiveness, legitimacy, and long-term sustainability.